A new species and two newly recorded species of the subgenus Pergalumna (Pergalumna) (Acari, Oribatida, Galumnidae) from China - Zheng, Qianfen; Liang, Wenqin; Ren, Guoru; Yang, Maofa (Zootaxa, 2019)
A new species, Pergalumna (Pergalumna) sidorchukae sp. nov., and two newly recorded species, Pergalumna (Pergalumna) jongkyui and Pergalumna (Pergalumna) amorpha, of oribatid mites of the subgenus Pergalumna (Pergalumna) from China, are described and illustrated in this study. The new species is similar to Pergalumna (Pergalumna) yurtaevi, but it differs from the latter by the surface of notogaster, the shape and size of notogastral porose areas, and the absence of postanal porose area.